Identification of a Novel Mutation in the SEC23B Gene Associated With Congenital Dyserythropoietic Anemia Type II Through the Use of Next-generation Sequencing Panel in an Undiagnosed Case of Nonimmune Hereditary Hemolytic Anemia. Issue 7 (October 2018) - Aydin Koker, Sultan; Karapinar, Tuba H.; Oymak, Yeşim; Bianchi, Paola; Fermo, Elisa; Gozmen, Salih; Vergin, Canan
Abstract : Congenital dyserythropoietic anemias (CDAs) are rare hereditary blood disorders characterized by ineffective erythropoiesis, hemolysis, and erythroblast morphologic abnormalities in the bone marrow. The 3 main types of CDA, I to III, and variant types of CDA, IV-VIII, have been described. The causative genes have been identified as CDAN1, C15ORF41, SEC23B, KIF23, KLF1, and GATA1 . CDA type II is the most frequent form. Typical symptoms are jaundice, hepatosplenomegaly, mild-to-severe normocytic anemia, and inadequate reticulocyte response. We report an 18-year-old boy who had chronic mild congenital anemia, jaundice, and splenomegaly mimicking nonautoimmune hemolytic anemia since 18 months of age. Compound heterozygous mutations in SEC23B gene were detected by the use of a gene-targeted next-generation sequencing panel: the already reported missense mutation c.40C>T (p.Arg14Trp), and a new frameshift deletion (c.489_489delG, p.Val164Trpfs*3), confirming the diagnosis of CDA type II. The study underlines the molecular heterogeneity of CDA II and the importance of a precise diagnosis in rare congenital diseases such as CDA II. In consequence, it can be difficult to diagnose because of limited resources, financial constraint, and rarity of disease in the developing country. Advanced laboratories and new molecular approaches may help in diagnosing rare anemias. Abstract : Supplemental Digital Content is available in the text.